Supramolecular synthon hierarchy in bumetanide cocrystals - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Novel cocrystals of sulfonamide drug Bumetanide with carboxamides are developed based on supramolecular synthons approach

Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.

Supramolecular synthon hierarchy in sulfonamide cocrystals with syn-amides and N-oxides - Bolla, Geetha; Nangia, Ashwini (IUCRJ, 2019)
Sulfonamide drugs are well known antibacterial and antimicrobial molecules for pharmaceutical development. Building a library of suitable supramolecular synthons for the sulfonamide functional group and understanding their crystal structures with partner coformer molecules continues to be a challenge in crystal engineering. Although a few sulfonamide cocrystals with amides and N-oxides have been reported, the body of work on sulfonamide synthons is limited compared with those that have carboxylic acids and carboxamides. To address this structural gap, the present work is primarily focused on sulfonamide-lactam and sulfonamide-syn-amide synthons with drugs such as celecoxib, hydrochlorothiazide and furosemide. Furthermore, the electrostatic potential of previously reported cocrystals has been recalculated to show that the negative electrostatic potential on the lactam and syn-amide O atom is higher compared with the charge on carboxamide and pyridine N-oxide O atoms. The potential of sulfonamide molecules to form cocrystals with syn-amides and lactams are evaluated in terms of the electrostatic potential energy for the designed supramolecular synthons.
Keywords: cocrystals; crystal engineering; sulfonamides; supramolecular synthons; syn-amides